2-Naphthyl Quinoxalin-2-yl Ether - Hassan, N.D.; Tajuddin, Hairul Anuar; Abdullah, Z.; Ng, S.W. (International Union of Crystallography, 2009)
In the crystal structure of the title compound, C(18)H(12)N(2)O, the two fused rings are aligned at 64.2 (1)degrees; the C-O-C angle is 118.73 (12)degrees.